Identificación de factores psicológicos asociados a la activación y a la inhibición se la sintomatología clínica de la fibromialgia. - Rodríguez Sastre, Ricardo (Acta Colombiana de Psicología, 2002)
This study tries to identify the psychological factors associated with stimulation and inhibition of the fibromyalgia´s clinical symptoms through a questionnaire made by the authors. The design was a descriptive correlation analyses.The instrument was applied to 60 women with fibromyalgia´s diagnostic, who where users of the Colombian Army Health Service. They were middle class and with primary school. The results showed that the fibromyalgia´s symptoms correspond to the half level of the percentage scale used. There was a significant association (P<0.05) between stressful situations and fibromyalgia´s activation symptoms, as well as, between social support plus self-care and fibromyalgia´s inhibition symptoms.There was a significant correlation (P<0.05) between fibromialgy´s clinical symptoms and depression and anxiety psychological factors.